Stratification of yerba mate seeds in a commercial nursery and the emergence monitoring - Cíntia Winhelmann, Mara; Gastmann, Julia; Jaime de Vargas, Leo; Vivian Zeni, Jader; Maria de Freitas, Elisete; Sidnei Fior, Claudimar (Scientia Agraria Paranaensis, 2021)
The propagation of Ilex paraguariensis A.St.-Hil. is carried out by seeds that have a low germination rate and morphophysiological dormancy. In order to increase the germination percentage, stratification treatments and emergence monitoring were tested. For this, yerba mate seeds were subjected to stratification treatments: Treatment 1 - seeds between two sand layers; Treatment 2 - seeds between two sand layers and commercial substrate covered with corn straw; Treatment 3 - seeds between two sand layers with the addition of 4.0 g of controlled-release fertilizer; Treatment 4 - seeds between two sand layers covered with corn straw; and a control treatment - seeds without stratification. The stratification period for all treatments was 180 days, and at 120, 150, and 180 days, 100 seeds were removed per repetition from each treatment for emergence tests, with weekly observation for 180-days in a completely randomized design. After that period, the tetrazolium test was performed with the seeds that did not emerge. At 120-days of stratification there was no emergence and at 150-days it was 0.83%. At 180-days, treatment 3 showed the highest percentage - 13.19%. Seeds without stratification do not germinate and after 180-days of emergence the amount of non-viable seeds increased in all treatments. Stratification in sand, combined with controlled-release fertilizer favors yerba mate seedlings emergence. After 180-days of emergence in germinator plants at 25°C, there is an increase in non-viable seeds amount. Seeds that did not undergo the stratification process do not germinate and present a higher dormant seeds percentage after 180-days of emergence.